AVRUPA BİRLİĞİ’NİN ÇEVRESEL ETKİ DEĞERLENDİRMESİ YÖNERGESİNE KISA BİR BAKIŞ - Abdurrahman Saygılı (Ankara Avrupa Çalışmaları Dergisi)
Environmental Impact Assessment is a tool that seeks to ensure sustainable development through the evaluation of those impact arising from project that likely to have significant environmental effecs. By requiring an environmental impact assessment before a development project begins, a decision-making authority/authorities creates the obligation to conduct an assessment of the potential consequences to human health and the environment. An important step in the development of an international practice of environmental assessment was the publication of Council Directive 85/337/EEC in 1985. Directive came into force in 1988. After that this Directive is amanded by 97HUEC. Certain projects in Directive are subject to mandatory assessment process (Annex I) , others are subject to an assessment if the Member States determined that “their characteristics so require” (AnnexII).GİRİŞAvrupa Birliği’nin temeli olan Avrupa Ekonomik Topluluğu’nu kuran antlaşmalardan 1972 Paris Zirvesi’nin yapılmasına kadar geçen süreçte çevre özel bir koruma rejimine sahip değildi.